Introduction to the special issue on "Critical reflections on management and organizations: a postcolonial perspective" - Bobby Banerjee, Subhabrata; Prasad, Anshuman (Critical perspectives on international business, 2008)
Purpose - The purpose of this paper is to present a short note on postcolonialism as a field of critical inquiry in the business management field, and enable the guest editors to introduce the contents of a special issue entitled "Critical reflections on management and organization: a postcolonial perspective".Design methodology approach - The paper states that postcolonial theory seeks to critique and analyze the complex and multifaceted dynamics of modern Western colonialism and to develop an in-depth understanding of the ongoing significance of the colonial encounter for people's lives both in the West and the non-West.Findings - The paper finds that modern western colonialism - a phenomenon with a history of roughly 500 years and a geographical reach that at one point spanned approximately 90 percent of the entire earth - is an episode of particular significance in human history.Originality value - The paper shows that the special issue contents reflect different aspects of contemporary issues in postcolonialism. In terms of postcolonial geographies, the special issue papers cover regions as diverse as Africa, Australia, China, India, Jordan, Malaysia, Poland, and the UK.